2007
DOI: 10.1080/13546800701614098
|View full text |Cite
|
Sign up to set email alerts
|

Deficient relational binding processes in adolescents with psychosis: Evidence from impaired memory for source and temporal context

Abstract: These findings suggest impaired relational binding processes in adolescents with psychosis, resulting in a difficulty to create unified memory representations. Our findings on retrospective confidence data point to impaired monitoring of retrieved information that may also impair memory performance in these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 77 publications
4
17
1
1
Order By: Relevance
“…First, in the recall test patients produced fewer studied words than controls, a result that is congruent with previous studies suggesting impaired conscious recollection in these patients (Brickman et al, 2004;Doré et al, 2007Doré et al, , 2009Fagerlund et al, 2006;Landro & Ueland, 2008;Roofeh et al, 2006;Ueland, Oie, Landro, & Rund, 2004a, 2004b. Most important, we found that patients recalled a similar proportion of targets and lures, whereas controls recalled more targets than critical lures.…”
Section: True and False Memories In Adolescent Psychosis 233supporting
confidence: 92%
See 1 more Smart Citation
“…First, in the recall test patients produced fewer studied words than controls, a result that is congruent with previous studies suggesting impaired conscious recollection in these patients (Brickman et al, 2004;Doré et al, 2007Doré et al, , 2009Fagerlund et al, 2006;Landro & Ueland, 2008;Roofeh et al, 2006;Ueland, Oie, Landro, & Rund, 2004a, 2004b. Most important, we found that patients recalled a similar proportion of targets and lures, whereas controls recalled more targets than critical lures.…”
Section: True and False Memories In Adolescent Psychosis 233supporting
confidence: 92%
“…Recent studies suggest that significant memory deficits are present in adolescent patients (Brickman et al, 2004;Fagerlund et al, 2006;Landro & Ueland, 2008;Oie, Sundet, & Rund, 1999;Roofeh et al, 2006), allowing early examination of the functional mechanisms putatively impaired in psychotic disorders. Importantly, memory deficits in young patients are reported regardless of the specific aetiology of psychosis, i.e., schizophrenia, bipolar disorder with psychotic features, or psychosis not otherwise specified (Doré, Caza, Gingras, Maziade, & Rouleau, 2009;Doré, Caza, Gingras, & Rouleau, 2007;McClellan, Prezbindowski, Breiger, & McCurry, 2004;Roofeh et al, 2006), suggesting common impairment to memory processes. Given that episodic memory deficits appear to threaten the functional outcome of patients, understanding how memory processes relate to psychosis at an early stage is essential for developing early and theoretically driven interventions (Fujii & Wylie, 2003;Green, Kern, Braff, & Mintz, 2000;Velligan, Bow-Thomas, Mahurin, Miller, & Halgunseth, 2000).…”
Section: Introductionmentioning
confidence: 97%
“…[Patalano und LeClair, 2011;Moritz und Van Quaquebeke, 2014;Yu et al, 2015]. Dieses 2-seitige Ergebnismuster (Überkonfidenz in Fehlentscheidungen, Unterkonfidenz für korrekte Entscheidungen bei Psychose) wurde in diversen Studien bestätigt [Bhatt et al, 2010;Doré et al, 2007;Gawęda et al, 2013;Köther et al, 2012;Mayer et al, 2014;Moritz et al, 2014dMoritz et al, , 2015aPeters et al, 2007Peters et al, , 2013; die Evidenz wurde kürzlich von Balzan [2016] in einer Übersichtsarbeit zusammengefasst. Die Überkonfi-denz in Fehlurteile, gepaart mit der niedrigen Konfidenz bei richtigen Urteilen, führt zu «Wissenskontamination» (definiert als das Verhältnis von hochkonfidenten falschen Antworten zu allen hochkonfidenten Antworten).…”
Section: Empirische Fundierungunclassified
“…Our task design also allowed us to examine whether any differences observed in binding ability between groups could be due to difficulties remembering individual stimulus features, in particular, words (Diaz-Asper et al, 2008;Dore, Caza, Gingras, & Rouleau, 2007) or voices (Hirano et al, 2010;McKay, Headlam, & Copolov, 2000, Zhang et al, 2008. This issue is important since the ability to process external voices is particularly impaired when hallucinations are more prominent, suggesting that the perception of both real and hallucinated voices draw on similar neural resources (Hugdahl et al, 2008;Vercammen, Knegtering, Bruggeman, & Aleman, 2011).…”
Section: Introductionmentioning
confidence: 98%